1995
DOI: 10.1182/blood.v85.12.3736.bloodjournal85123736
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by interleukin-10 of inducible cyclooxygenase expression in lipopolysaccharide-stimulated monocytes: its underlying mechanism in comparison with interleukin-4

Abstract: Both interleukin-10 (IL-10) and IL-4 inhibited the prostanoid synthesis of lipopolysaccharide (LPS)-stimulated human monocytes, and their inhibition was shown to be based on a common mechanism to suppress the gene expression of inducible cyclooxygenase (COX). COX has been shown to exist in at least two distinct isoforms, designated COX-1 and COX-2, and their gene expressions exhibit different profiles. At both the protein and mRNA levels, the expression of COX-1 was constitutive and was not modulated by treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(27 citation statements)
references
References 43 publications
3
23
0
1
Order By: Relevance
“…A previous report has shown that BA inhibits the expression of cyclooxygenase 2 (COX-2) expression in cultures of human peripheral blood mononuclear cells, leading to a decrease in PGE2 production [22]. The increase in IL-10 induced by BA described in our study may be related to the inhibition of PGE 2 production, another inflammatory mediator in LPS-challenged mice, since IL-10 is known to inhibit COX2 expression by LPS-stimulated monocytes [23]. Thus, we are establishing the role of another molecule involved in the anti-inflammatory activity produced by BA.…”
Section: Discussionsupporting
confidence: 64%
“…A previous report has shown that BA inhibits the expression of cyclooxygenase 2 (COX-2) expression in cultures of human peripheral blood mononuclear cells, leading to a decrease in PGE2 production [22]. The increase in IL-10 induced by BA described in our study may be related to the inhibition of PGE 2 production, another inflammatory mediator in LPS-challenged mice, since IL-10 is known to inhibit COX2 expression by LPS-stimulated monocytes [23]. Thus, we are establishing the role of another molecule involved in the anti-inflammatory activity produced by BA.…”
Section: Discussionsupporting
confidence: 64%
“…Our in vitro studies suggested that unlike other tissue MA, splenic MA in inflammation may not release PGE 2 in proportion to increased COX-2 expression [21]. Furthermore, endogenous IL-10, an immunosuppressive cytokine reported to inhibit COX-2 expression in bone marrow MA, peritoneal MA, neutrophils, and cancer cells [22,23], did not significantly modify COX-2 expression by these in vitro splenic MA [21].…”
Section: Introductionmentioning
confidence: 74%
“…The important direct downstream targets of Stat‐3 are not yet clearly defined, although an additional signal, mediated by the carboxy‐terminal region of the IL‐10R1, is required for the antiinflammatory effects of IL‐10 signaling (44). Antiinflammatory targets include the down‐regulation of a variety of cytokines, chemokines, and inflammatory molecules, including IL‐1, IL‐6, and TNFα, as well as COX‐2 in macrophages (17, 45–48). The IL‐10 effect on these target molecules involves decreased transcription, as well as increased catabolism of the transcripts (47–50).…”
Section: Discussionmentioning
confidence: 99%